Normalised adaptive linear element‐based control of single‐phase self excited induction generator feeding fluctuating loads. Issue 8 (1st August 2014) - Kalla, Ujjwal Kumar; Singh, Bhim; Murthy, S.S.
Abstract : In this study, a new normalised adaline‐based control algorithm is proposed to control voltage source converter (VSC) used for voltage control and harmonics mitigation of two‐winding asymmetric single‐phase self excited induction generator (SEIG) feeding fluctuating linear and non‐linear loads. The proposed control algorithm is implemented on a digital signal processor (DSP). In the proposed SEIG system, a two‐winding asymmetric single‐phase SEIG is driven by a speed governor controlled diesel/biogas engine. The VSC is used for adjustable fundamental reactive current compensation of a two‐winding single‐phase SEIG for voltage control, and harmonics elimination of variety of loads. An insulated gate bipolar transistor‐based two‐leg VSC is connected at the point of common coupling. The proposed new control algorithm has many distinct advantages such as fast response which is highly desirable for fluctuating loads and fast convergence at all frequency components. The mathematical formulation of the proposed control algorithm is given and recorded test results of the SEIG system are presented to demonstrate the voltage control, harmonics mitigation and fast response of the algorithm. The proposed controller of single‐phase SEIG system is designed, developed and implemented on a DSP to validate the claims. A MATLAB simulation model of SEIG system with proposed controller is also developed and simulated results are presented along with the test results to validate the model developed.